A behavioural theory of the fund management firm. Issue 11 (1st September 2016) - Holland, John
Abstract : The paper outlines a behavioural theory of the fund manager (FM) firm comprising investment decisions (at stock and portfolio levels) by teams and individuals, and of an organisation process and contextual resource factors affecting decisions. FM organisational processes interacted with resources to enhance investment team decision conditions, costs and processes. Enhanced conditions and reduced decision costs were expected to improve the chances of FM success via new information production and better-quality decisions. These dynamic elements to FM firms can be interpreted as tentative organisational means to deal with major problems of behaviour, uncertainty and information asymmetry at the heart of the valuation, investment and performance problems facing FMs. Field research was conducted in 15 FM firms during 2004–2011. A grounded theory approach was employed in processing the data. This led to improvements in empirical understanding of behaviour within FM firms and markets. The results were discussed relative to relevant literature and previous grounded theory. This created a new conceptual tool to investigate FM underperformance and variety in FM styles. The paper demonstrated an empirically rich model of hierarchy, information production, capital allocation and other resource usage in financial institutions and discussed how this created further opportunities for research.